Situs inversus totalis: A case report from Somalia - Abdirahman Ibrahim Said; Abdirahman Omer Ali; Amtarahman Ibrahim Said; Said Ibrahim Said; Hassan Sh Abdirahman Elmi (Atención Primaria Práctica)
Introduction: Situs inversus totalis (SIT), a rare congenital disorder, involves complete reversal of the heart's position and mirrored arrangement of visceral organs. Early diagnosis is crucial for managing complications like transposition of the great vessels and Kartagener syndrome, marked by bronchiectasis and sinusitis due to ciliary dysfunction. Case presentation: A 52-year-old male with diabetes mellitus presented with large amounts of watery diarrhea, vomiting, dizziness, and palpitations. He managed his diabetes with 70 units of insulin daily and had a history of chronic obstructive pulmonary disease. Physical examination revealed hypotension, tachycardia, and a right-sided apex beat. Investigations, including chest X-ray, ultrasound, and ECG, confirmed dextrocardia with situs inversus and hypovolemic shock secondary to acute gastroenteritis. The patient responded well to treatment and was discharged on the second day, continuing diabetic management. Discussion: SIT is a genetically determined anomaly with an incidence ranging from 1:35 000 to 1:1400, averaging 1:10 000, with a higher prevalence in males. Many patients are asymptomatic, with the condition often detected incidentally. Diagnostic imaging techniques, including chest radiography, CT scans, MRI, and ultrasonography, are crucial in confirming SIT. ECG findings, such as right-axis deviation and reversed QRS complexes, are valuable in diagnosing dextrocardia. Patient education is essential to empower individuals with SIT to navigate their healthcare, prevent complications, and reduce anxiety. Conclusion: SIT poses diagnostic challenges due to its incidental discovery. Accurate diagnosis relies on thorough imaging and clinical evaluation. Patient education is vital for informed care and anxiety reduction. Case reviews underscore the importance of healthcare providers' readiness to diagnose SIT effectively despite unrelated symptoms. Resumen: Introducción: Situs inversus totalis, un trastorno congénito raro, implica la inversión completa de la posición del corazón y la disposición en espejo de los órganos viscerales. El diagnóstico temprano es crucial para manejar complicaciones como la transposición de los grandes vasos y el síndrome de Kartagener, caracterizado por bronquiectasias y sinusitis debido a la disfunción ciliar. Presentación del Caso: Un hombre de 52 años con diabetes mellitus presentó grandes cantidades de diarrea acuosa, vómitos, mareos y palpitaciones. Controlaba su diabetes con 70 unidades de insulina diarias y tenía antecedentes de EPOC. El examen físico reveló hipotensión, taquicardia y un latido apical en el lado derecho. Las investigaciones, incluyendo radiografía de tórax, ecografía y ECG, confirmaron dextrocardia con situs inversus y choque hipovolémico secundario a gastroenteritis aguda (AGE). El paciente respondió bien al tratamiento y fue dado de alta al segundo día, continuando con el manejo de la diabetes. Discusión: SIT es una anomalía determinada genéticamente con una incidencia que varía de 1:35,000 a 1:1400, promediando 1:10,000, con una mayor prevalencia en hombres. Muchos pacientes son asintomáticos, con la condición a menudo detectada incidentalmente. Las técnicas de diagnóstico por imagen, incluyendo radiografía de tórax, tomografías computarizadas, resonancia magnética y ultrasonografía, son cruciales para confirmar SIT. Los hallazgos del ECG, como la desviación del eje derecho y los complejos QRS invertidos, son valiosos para diagnosticar la dextrocardia. La educación del paciente es esencial para empoderar a las personas con SIT a navegar su atención médica, prevenir complicaciones y reducir la ansiedad. Conclusión: Situs inversus totalis (SIT) presenta desafíos diagnósticos debido a su descubrimiento incidental. Un diagnóstico preciso depende de una evaluación clínica e imagenológica exhaustiva. La educación del paciente es vital para una atención informada y la reducción de la ansiedad. Las revisiones de casos subrayan la importancia de que los proveedores de atención médica estén preparados para diagnosticar SIT de manera efectiva a pesar de los síntomas no relacionados.